Sistema mobile para o auxílio na localização e deslocamento à farmácias abertas - Parzianello, Samuel Inácio (2020)
This work aimed to develop an application for Android devices that provides the user with an updated listing of pharmaceutical establishments that are open in the region. Its development was carried out following standardization and good software development practices acquired during the school period. We highlight the use of the following technologies for the development of the application: Android development languages and real-time database distributed by Google (Firebase Realtime Database).